Breast and pancreatic cancer interrupt IRF8-dependent dendritic cell development to overcome immune surveillance - Melissa A. Meyer (Nature Portfolio, 2018)
Tumors escape the immune system through many mechanisms. Here the authors show that certain tumors inhibit anti-tumor immunity by stopping the production of conventional dendritic cells (cDCs) in the bone marrow, therefore depleting the pool of cDCs available to present antigen to CD8+ T cells.